Implementation of Social and Environmental Responsibility at The State Electricity Company (PT PLN Persero) Bangka Belitung Regional Parent Unit in Improving Pangkalpinang Nature School Education - Aprilia Dini Rosani; Ardiyansah Ardiyansah; Salim Yusuf Sailan; Zulkarnain Zulkarnain (Jurnal Indonesia Sosial Sains, 2024)
In line with the 2005-2025 National Medium-Term Development Plan (RJPM), PT PLN (Persero) Unit Induk Wilayah Bangka Belitung is dedicated to making improvements in four key areas: overall enhancements, improving the quality of education, promoting educational development, making educational administration more efficient. This research describes how the Corporate Social and Environmental Responsibility (CSR) program by PT PLN UIW Bangka Belitung is being implemented for the Kacang Pedang Sub-district, Gerunggang, Pangkalpinang City community. The study uses a qualitative method and John Elkington's triple bottom-line theory. The results show that the TJSL program by PT PLN (Persero) Unit Induk Wilayah Bangka Belitung provides significant benefits for the education of the Kacang Pedang community in Pangkalpinang City by supplying facilities and infrastructure for the Sekolah Alam Pangkalpinang program.